Effects of Exercise-Based Interventions on Postpartum Depression: A Meta-Analysis of Randomized Controlled Trials - Garcia-Hermoso, A (Blackwell Publishing Inc., 2017)
Background: There is inconsistent evidence about the effect of physical activity on the prevention and treatment of depression during the postnatal period. The aim of this meta-analysis was to determine the effect of physical activity interventions during pregnancy and the postpartum period for controlling postpartum depressive symptoms. Methods: We systematically searched Cochrane Library Plus, Science Direct, EMBASE, CINAHL, PubMed, Web of Science, and Scopus, from January 1990 to May 2016, for randomized or nonrandomized controlled trials addressing the effect of physical activity on postpartum depression. The inverse variance-weighted method was used to compute pooled estimates of effect size and respective 95% confidence intervals (95% CI) for physical activity intervention on postpartum depression. Subgroup analyses were performed comparing women with and without postpartum depressive symptoms according to specific scales measuring this construct. Meta-regression and sensitivity analysis were computed to evaluate heterogeneity. Results: Twelve studies were included in the meta-analysis. Effect size for the relationship between physical activity interventions during pregnancy and the postpartum period on postpartum depressive symptoms was 0.41 (95% CI 0.28-0.54). Heterogeneity was I2 = 33.1% (P =.117). When subgroup analyses were done, pooled effect sizes were 0.67 (95% CI 0.44-0.90) for mothers who met postpartum depressive symptoms criteria at baseline based on specific scales, and 0.29 (95% CI 0.14-0.45) for mothers who did not meet those depressive symptoms criteria at baseline. Conclusion: Physical exercise during pregnancy and the postpartum period is a safe strategy to achieve better psychological well-being and to reduce postpartum depressive symptoms. © 2017 Wiley Periodicals, Inc.